A graphite oxide (GO)-based remote readable tamper evident seal. (8th September 2015) - Cattaneo, A; Bossert, J A; Guzman, C; Haaker, A; Gupta, G; Mohite, A; Dumont, J H; Purdy, G M; Miller, K A; Marchi, A N; Farrar, C R; Mascareñas, D D L
Abstract: This paper presents a prototype of a remotely readable graphite oxide (GO) paper-based tamper evident seal. The proposed device combines the tunable electrical properties offered by reduced graphite oxide (RGO) with a compressive sampling scheme. The benefit of using RGO as a tamper evident seal material is the sensitivity of its electrical properties to the common mechanisms adopted to defeat tamper-evident seals. RGO's electrical properties vary upon local stress or cracks induced by mechanical action (e.g., produced by shimming or lifting attacks). Further, modification of the seal's electrical properties can result from the incidence of other defeat mechanisms, such as temperature changes, solvent treatment and steam application. The electrical tunability of RGO enables the engraving of a circuit on the area of the tamper evident seal intended to be exposed to malicious attacks. The operation of the tamper evident seal, as well as its remote communication functionality, is supervised by a microcontroller unit (MCU). The MCU uses the RGO-engraved circuitry to physically implement a compressive sampling acquisition procedure. The compressive sampling scheme provides the seal with self-authentication and self-state-of-health awareness capabilities. The prototype shows potential for use in low-power, embedded, remote-operation non-proliferation security related applications.